Experimentally induced, synergistic late effects of a single dose of radiation and aging: significance in LKS fraction as compared with mature blood cells. Issue 3 (21st November 2014) - Hirabayashi, Yoko; Tsuboi, Isao; Nakachi, Kei; Kusunoki, Yoichiro; Inoue, Tohru
Abstract The number of murine mature blood cells recovered within 6 weeks after 2‐Gy whole‐body irradiation at 6 weeks of age, whereas in the case of the undifferentiated hematopoietic stem/progenitor cell (HSC/HPC) compartment [cells in the lineage‐negative, c‐kit‐positive and stem‐cell‐antigen‐1‐positive (LKS) fraction], the numerical differences between mice with and without irradiation remained more than a year, but conclusively the cells showed numerical recovery. When mice were exposed to radiation at 6 months of age, acute damages of mature blood cells were rather milder probably because of their maturation with age; but again, cells in the LKS fraction were specifically damaged, and their numerical recovery was significantly delayed probably as a result of LKS‐specific cellular damages. Interestingly, in contrast to the recovery of the number of cells in the LKS fraction, their quality was not recovered, which was quantitatively assessed on the basis of oxidative‐stress‐related fluorescence intensity. To investigate why the recovery in the number of cells in the LKS fraction was delayed, expression levels of genes related to cellular proliferation and apoptosis of cells in the bone marrow and LKS fraction were analyzed by real‐time polymerase chain reaction (RT‐PCR). In the case of 21‐month‐old mice after radiation exposure, Ccnd1, PiK3r1 and Fyn were overexpressed solely in cells in the LKS fraction. Because Ccnd1and PiK3r1 upregulated by aging were further upregulated by radiation, single‐dose radiation seemed to induce the acceleration of aging, which is related to the essential biological responses during aging based on a lifetime‐dependent relationship between a living creature and xenobiotic materials. Copyright © 2014 John Wiley & Sons, Ltd.